Ancient Turkic mythology epic about his son Baybori Bamsу-Bayrek. - Abzhet., B. S.; Yildirim., Z. (Journal of Oriental Studies, 2016)
In the article the ancient plots of shamanistic beliefs and mythical elements of Turkic people and ancient beliefs of Oguz tribes are examined that had in an epos, overcoming Bamsy-Bairek on "Book of my grandfather Korkut".